Identity and Otherness in the Rahab Story. Analysis of the Rahab Speech (Josh 2:9–11) - Toczyski, Andrzej (The Biblical Annals, 2024)
The biblical story of Rahab of Jericho was included in the Book of Joshua to serve a specific purpose in a remote historical context. This article focuses on a possible function of the Rahab story, which might have been employed by the author/redactor as a literary pattern for cross-cultural encounters between different groups, such as the Canaanite clan of Rahab and the Israelites. The Deuteronomistic Law demands the removal of “others” and separation from them, while Rahab, “the outsider,” is saved and protected by the Israelites. This fact may not only prove the benevolence of the Israelites but also be evidence of a recurring literary pattern of constructing national and religious self-identity first through retelling and eventually rewriting stories. Since the Rahab story has been read/heard by ancient audiences and by many readers through the centuries, this pattern may also prove relevant for contemporary readers by providing grounds for intercultural dialogue in the modern world.